Personalidad y violencia. - Cordovilla Sinche, Silvia Patricia (2015)
This research work aims to identify the cognitive schemata that induce man to violence against their partner. The theoretical foundation that supports research, is the cognitive-behavioural Approach, which is in charge of the cognitive processes distorted that originate from the children, taking as a result the alteration of behavior and the development of the personality. The case analysis is carried out under the mixed-mode, and descriptive, lets you collect information for the object of study in a logical and sequential order, corresponds to a study of biographical and bibliographical type, which allows you to collect information of the individual, life history and interpretations elapsed in different stages of the life cycle, using bibliographic material, such as scientific journals, books and web pages. The sample selected is a young man of 23 years of age, who was the victim and witness of abuse in his childhood, which has impacted until now. The instruments used for obtaining information are: the semi-structured interview, Personologica History, Inventory of Automatic Thoughts of Ruiz and Lujan and the Questionnaire of aggression of Buss and Perry. The results obtained show that the individual presents cognitive schemata that are distorted: psychological deprivation, lack of communication, resentment toward their parents, irrational beliefs relating to the female sex, fallacy of control, emotional reasoning, fallacy of change, the should and fallacy of reason, generating physical aggression, verbal and psychological. In addition it was found that the hostile environment in which he lived in the children and the aggression of which was the victim and witness, predisposed the patient develop irrational thoughts and generate violence toward their partner. Therefore it is recommended that the subjects who generate domestic violence should receive urgent professional psychological intervention, with the purpose to prevent their diagrams distorted they commit serious crimes.